Transfusion‐associated graft‐versus‐host disease in a liver transplant recipient: an unusual presentation and review of the literature. Issue 1 (7th May 2012) - O'Brien, Kerry L.; Pereira, Shalini E.; Wagner, Jeffrey; Shadman, Mazyar; Hendrie, Paul; Nelson, Karen; Gernsheimer, Terry B.; Price, Thomas; Reyes, Jorge D.; Nester, Theresa
<x xml:space="preserve">Abstract</x> BACKGROUND: Transfusion‐associated graft‐versus‐host disease (TA‐GVHD) is a rare, nearly universally fatal complication from transfusion of nonirradiated cellular blood components, occurring when a recipient's immune system is unable to recognize and destroy transfused T lymphocytes. Irradiation of cellular components eliminates this risk. We present an unusual case of a liver transplant recipient developing TA‐GVHD 13 weeks after transfusion of a random unit of nonirradiated red blood cells (RBCs) that happened to be from a donor homozygous for an HLA haplotype shared by the patient. STUDY DESIGN AND METHODS: This study was a single case review of a liver transplant recipient who developed skin GVHD and marrow aplasia. Clinical course and the chimerism studies involving the patient, the liver donor, and the blood donor are detailed. RESULTS: The patient presented 3 months posttransplant with GVHD of his skin and marrow aplasia. In addition to standard antigraft immunosuppression, this patient had started the interleukin‐1 receptor antagonist anakinra on Posttransplant Day 13 for an acute gout flare. Chimerism studies on the patient's peripheral blood identified a population of CD3 cells that did not originate with either the patient or his liver donor. HLA studies and microsatellite profiling of the unknown CD3 population identified the source of the patient's TA‐GVHD, a unit of nonirradiated, nonleukoreduced apheresis RBCs. CONCLUSION: Use of an immunomodulating agent may have contributed to the development of TA‐GVHD in a liver transplant patient who received a random unit of nonirradiated RBCs by chance from an unrelated haploidentical donor.